Management of cochlear implant device extrusion: case series and literature review. Issue 2 (July 2014) - Geraghty, M; Fagan, P; Moisidis, E
Abstract Introduction and aims: Cochlear implants have enabled an improved quality of life for many patients with deafness. Implant extrusion and skin flap necrosis are the most common complications associated with implant use. We report our management of patients presenting with complications as a result of cochlear implant insertion. The goal of surgery was to achieve a stable, healed wound for use as a cochlear device implantation site. Methods and results: We describe a series of patients presenting with skin flap necrosis and/or extrusion of their cochlear implant. The reconstructive options employed are discussed. Conclusion: Surgeons should be aware of the reconstructive options available in such circumstances, and should choose appropriate management depending on the clinical situation, in order to optimise the functional result for the patient.